2013
DOI: 10.1021/ac403061n
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Target Detection Using DNA-Binding Dye Chemistry in Droplet Digital PCR

Abstract: Two years ago, we described the first droplet digital PCR (ddPCR) system aimed at empowering all researchers with a tool that removes the substantial uncertainties associated with using the analogue standard, quantitative real-time PCR (qPCR). This system enabled TaqMan hydrolysis probe-based assays for the absolute quantification of nucleic acids. Due to significant advancements in droplet chemistry and buoyed by the multiple benefits associated with dye-based target detection, we have created a "second gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
129
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(132 citation statements)
references
References 49 publications
(84 reference statements)
0
129
0
Order By: Relevance
“…In ddPCR, each PCR reaction is compartmentalized to allow the direct measurement of target sequences based on limiting dilution (23 ). The use of TaqMan hydrolysis probes in ddPCR assays enables genotyping by allelic discrimination and, if necessary, absolute quantification (24 -26 ).…”
Section: © 2016 American Association For Clinical Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…In ddPCR, each PCR reaction is compartmentalized to allow the direct measurement of target sequences based on limiting dilution (23 ). The use of TaqMan hydrolysis probes in ddPCR assays enables genotyping by allelic discrimination and, if necessary, absolute quantification (24 -26 ).…”
Section: © 2016 American Association For Clinical Chemistrymentioning
confidence: 99%
“…The probe-free ddPCR workflow adopted for the genotyping of DIPs in this study was similar to that used in a previously published protocol (23 ). Conditions were standardized across all 6 assays.…”
Section: Genotyping By Probe-free Ddpcrmentioning
confidence: 99%
See 1 more Smart Citation
“…The plate was heat-sealed with foil and placed in a conventional thermal cycler. Thermal cycling conditions for EvaGreen assays were as follows: 95 C for 5 minutes, then 40 cycles of 95 C for 30 seconds and 58 C for 1 minute (ramping rate reduced to 2%), and three final steps at 4 C for 5 minutes, 90 C for 5 minutes, and a 4 C indefinite hold to enhance dye stabilization (11). Thermal cycling conditions for TaqMan assays were as follows: 95 C for 10 minutes, then 40 cycles of 95 C for 15 seconds and 60 C for 1 minute (ramping rate reduced to 2%), and a final inactivation step at 98 C for 10 minutes.…”
Section: Ddpcr Workflowmentioning
confidence: 99%
“…In particular, Hindson and colleagues (10) found that, for quantifying circulating miRNAs, a prototype of the QX100 Droplet Digital PCR system (Bio-Rad Laboratories) was superior to qPCR carried out with TaqMan miRNA assays (Applied Biosystems and Life Technologies). Now, a second-generation instrument (named QX200) has been developed that is able to detect both TaqMan probe and DNA-binding dye chemistries with comparable precision and accuracy (11). In that work, ddPCR using the recently commercialized EvaGreen DNA-binding dye was shown to be comparable with TaqMan assays for quantification of mRNA; however, miRNA was not investigated.…”
Section: Introductionmentioning
confidence: 99%